The Influence of Academic Stress on Academic Performance among University Students - Li, Tan Xue; Lin, Tan Tze; Xin, Tan Hui; Wardhani, Sukma Tri Kusuma (Asia Pacific Journal of Management and Education (APJME), 2023)
Stress can be broadly defined as the response of the body when one cannot adapt to a situation when they feel under pressure or tension. This may affect students' lives and significantly impact their academic performance. This study took place at universities in Malaysia and Indonesia. Data collection using random sampling method (or stratified sampling method), 200 students were involved in this study. Questionnaires consisting of the Perceived Stress Scale and Student Life Satisfaction Scale were used to collect data for this study. This study aimed to determine the relationship between stress and academic performance among university students. This data was measured using descriptive statistical techniques, analysis of the factors that cause stress, the chi-square test, and the multivariate analysis of variance (MANOVA) model. From the data that has been tested, researchers suggest that the level of stress and life satisfaction among university students is different. Students with high grades have lower stress levels than students who do not, and the majors they take, the stress level, and life satisfaction of students majoring in Management and majoring in Medicine are different.